Seasonal variation in thermoregulation, locomotor performance, and field hydration in the snouted treefrog Scinax fuscovarius (Hylidae) - Silva, Nycolle Agnys Oliveira da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Amphibians, due to being ectothermic and having permeable skin, are especially sensitive to variations in environmental temperature and water availability. Thus, in Neotropical regions with markedly seasonal climates, the activity of many amphibians may be temporally restricted to the warmer and wetter months of the year. Some species, however, seasonally adjust both their thermoregulatory behavior and the thermal sensitivity of various physiological processes, allowing them to remain active throughout the seasons. These adjustments may involve seasonal changes in behaviors and in the costs associated with thermoregulation, as well as in the thermal sensitivity of behavioral performance. Finally, periods of low water availability may expose amphibians to excessive water loss and increase the potential risk of dehydration. In this context, we investigated seasonal variation in thermoregulatory behavior, field hydration state, and locomotor performance of the Scinax fuscovarius treefrog. Although this species concentrates its activity in spring and summer, it remains active year-round, including during the coldest and driest months. We measured the frogs' body temperature in the field (Tb) and the distribution of operative temperatures (Te) in their microhabitats, which allowed us to estimate thermoregulatory costs. We also determined their hydration level in the field and the thermal sensitivity of their locomotor performance. The study was conducted in the municipality of Rio Claro, SP, southeastern Brazil, where the climate is characterized by alternating hot-wet (spring and summer) and cold-dry (autumn and winter) seasons. Tb was lower in the cold-dry season (21.2 °C) than in the hot-wet season (26 °C). Operative temperatures (Te) decreased by an average of 6.5 °C during the cold-dry season, reducing the thermal quality (de) of the microhabitats. Despite this, the species maintained a Tb above Te in both seasons, reflecting high thermoregulatory accuracy (db), i.e., Tb remained close to the seasonal preferred temperature range (Tset). As a result, thermoregulatory effectiveness (E) was high (> 0.5), indicating active thermoregulation by the frogs in both seasons. The animals maintained high hydration levels (~98.7%) in both seasons. Locomotor performance varied seasonally, with reductions in optimal temperature (Topt), maximum performance (Pmax), and the 80% optimal performance range (B80) during the cold-dry season. Additionally, B80 was broader in winter. Our results indicate that S. fuscovarius exhibits important seasonal adjustments in its thermoregulatory behavior that compensate, at least partially, for the seasonal reduction in the thermal quality of its environment during the cold and dry season. On the other hand, seasonal differences in water availability did not affect the frog’s hydration state. Finally, we found that locomotor performance significantly decreases during autumn-winter, which may be reflected in the lower level of activity displayed by this species during this period.

Anfíbios, por serem ectotérmicos e possuírem pele permeável, são especialmente sensíveis às variações de temperatura e disponibilidade de água no ambiente. Assim, em regiões Neotropicais de clima marcadamente sazonal, a atividade de muitos anfíbios pode estar restrita temporalmente aos meses mais quentes e úmidos do ano. Algumas espécies, porém, ajustam sazonalmente tanto seu comportamento termorregulatório quanto a sensibilidade térmica de diferentes processos fisiológicos, permitindo a manutenção de suas atividades ao longo das estações. Esses ajustes podem envolver alterações sazonais nos comportamentos e custos associados à termorregulação e também na sensibilidade térmica do desempenho comportamental. Finalmente, períodos com baixa disponibilidade de água podem expor os anfíbios a uma perda excessiva de água e aumentar o risco potencial de desidratação. Neste contexto, nós investigamos a variação sazonal no comportamento termorregulatório, estado de hidratação em campo e do desempenho locomotor da perereca de banheiro, Scinax fuscovarius. Embora essa espécie concentre suas atividades na primavera e verão, ela permanece ativa ao longo do ano, inclusive durante os meses mais frios e secos do ano. Nós determinamos a temperatura corpórea dos animais em campo (Tc) e a distribuição de temperaturas operativas (Te) em seus microambientes, o que nos permitiu estimar os custos termorregulatórios. Também determinamos o grau de hidratação em campo e a sensibilidade térmica do desempenho locomotor. O estudo foi realizado no município de Rio Claro, SP, sudeste do Brasil, onde o clima pode ser caracterizado pela alternância de uma estação quente-úmida (primavera e verão) e outra fria-seca (outono e inverno). A Tc foi menor na estação fria-seca (21,2 °C) do que na quente-úmida (26 °C). As temperaturas operativas (Te) diminuíram, em média 6,5°C durante a estação frio-seca, o que reduziu a qualidade térmica (de) dos microhabitats. Apesar disso, a espécie manteve uma Tc acima da Te em ambas as estações, refletindo alta precisão termorregulatória (db), ou seja, Tc próxima ao intervalo sazonal de temperaturas preferidas (Tpref). Como resultado, a eficácia da termorregulação (E) foi alta (> 0.5), indicando termorregulação ativa das pererecas nas duas estações. Os animais mantiveram altos níveis de hidratação (~98,7%) em ambas as estações. O desempenho locomotor variou sazonalmente, com redução na temperatura ótima (Topt), no desempenho máximo (Pmax) e na faixa ótima de desempenho 80% (B80) durante a estação frio-seca. Além disso, a B80 foi mais ampla no inverno. Nossos resultados indicam que S. fuscovarius exibe ajustes sazonais importantes em seu comportamento termorregulatório que compensam, ainda que parcialmente, a redução sazonal da qualidade térmica do seu ambiente durante a estação fria e seca do ano. Por outro lado, diferenças sazonais na disponibilidade de água não afetaram o estado de hidratação das pererecas. Finalmente, nós encontramos que o desempenho locomotor diminui significativamente durante o outono-inverno, o que pode estar refletido no menor nível de atividade exibido por essa espécie durante este período.
Variação sazonal na termorregulação, desempenho locomotor e hidratação em campo da perereca-de-banheiro, Scinax fuscovarius (Hylidae)
Keywords: Anfíbios; Sazonalidade; Qualidade térmica do habitat